Réponses

  • Utilisateur Brainly
2014-03-08T16:54:53+01:00

5x² -10x-75=5(x-5)(x+3)
5(x-5)(x+3)
5(x²-5x+3x-15)
5(x²-2x-15)
5x²-10x-75

( -75/x+35)-(-5x+45)=[5(x-5)(x+3)]/x

(5(x-5)(x+3))/x
(5x²-10x-75)/x
5x-10-75/x
(-75/x+35)-(-5x+45)
  • Utilisateur Brainly
2014-03-08T17:08:39+01:00
Soit :
A= 5x² -10x -75
B= 5(x-5) (x+3)

On développe B:

B= 5(x-5) (x+3)
B= 5 (x² + 3x -5x -15)
B= 5x² -10x -75

A=B
donc 5x²-10x -75 = 5(x-5) (x+3)

On sait que 5x² -10x -75 = 5(x-5) (x+3)

Donc : ( 5 (x-5) (x+3) )/x = (5x² -10x-75) / x

On développe: (-75/x + 35) - (-5x+45)

-75/x +35 +5x -45 
-75/x + 5x²/x -10x/x
(5x² -10x -75) /x

On constate donc que (-75/x + 35) - (-5x+45) = ( 5 (x-5) (x+3) ) /x

Voilà ! J'espère t'avoir aidé(e) ! :)